Comparative study between Moroccan water strategies and WFD - Choukr-Allah R. (Dialogues on Mediterranean water challenges: Rational water use, water price versus value and lessons learned from the European Water Framework Directive, 2011)
Water resources in Morocco are limited, and irregular in time and space. Furthermore, the water resources undergo a deterioration of their quality by the various pollutant emissions, such as domestic and industrial wastewater. On the other hand, these resources are increasingly scarce due to a continued growth in demand. A new water law has come into force in 1995 that provides a comprehensive framework for integrated water management. This new law constitutes an efficient juridical tool to develop considerable efforts for water use and mobilization in order to make them compatible with aspirations of socio-economic development of Morocco in the 21 century. The Water Law has a number of similarities to the Water Framework Directive. For example it specifies the establishment of Basin Agencies which evaluate, plan and manage the water resources in their respective river basin, in order to strengthen the institutional arrangements of water management. Other principles stated in the Law are; 1) water as a public domain, 2) regulation of development, distribution, and sale of potable water, 3) improvement of agricultural water development and use, and 4) security against illegal water resources development, or conduct which causes water pollution. The paper concludes that including water demand management in Moroccan water policy has required major changes in the institutional arrangements.
3. MELIA Workshop Water Value Impacts on the Mediterranean Water Policies, 2009/03/21-23, Istanbul (Turkey); 4. MELIA Workshop Benchmarking Exercise and Recommendations on the Application of the Water Framework Directive, 2010/03/21-26, Amman (Jordan)